2015
DOI: 10.1130/g36616.1
|View full text |Cite
|
Sign up to set email alerts
|

Kelp, cobbles, and currents: Biologic reduction of coarse grain entrainment stress

Abstract: Models quantifying the onset of sediment motion do not typically account for the effect of biotic processes because they are difficult to isolate and quantify in relation to physical processes. Here we investigate an example of the interaction of kelp (Order Laminariales) and coarse sediment transport in the coastal zone, where it is possible to directly quantify and test its effect. Kelp is ubiquitous along rocky coastlines and the impact on ecosystems has been well studied. We develop a physical model to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Put simply, the use of a single value of critical Shields stress in the prediction of bed load flux does not fully capture the complex processes that control bed load transport rates. Previous studies have shown that variability in critical shear stress may be due to changes in bed pocket geometry [ Wiberg and Smith , ; Kirchner et al ., ], grain exposure and protrusion [ Fenton and Abbott , ; Kirchner et al ., ], bed grain size distribution [ Parker and Sutherland , ; Ferguson , ; Wilcock and Crowe , ], channel slope [ Lamb et al ., ], and even biological organisms [ Albertson et al ., ; Masteller et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Put simply, the use of a single value of critical Shields stress in the prediction of bed load flux does not fully capture the complex processes that control bed load transport rates. Previous studies have shown that variability in critical shear stress may be due to changes in bed pocket geometry [ Wiberg and Smith , ; Kirchner et al ., ], grain exposure and protrusion [ Fenton and Abbott , ; Kirchner et al ., ], bed grain size distribution [ Parker and Sutherland , ; Ferguson , ; Wilcock and Crowe , ], channel slope [ Lamb et al ., ], and even biological organisms [ Albertson et al ., ; Masteller et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Fine sediments and sedimentation may reduce habitat suitability for these sessile organisms by inhibiting feeding strategies. Large kelps such as A. clathratum additionally require a stable foundation for holdfast attachment to endure currents and storm surge (Morrison et al, 2009;Watanabe et al, 2014;Masteller et al, 2015). In contrast, E. parma would preferentially inhabit coarse sand areas (Stanley and James, 1971;Sisson et al, 2002), enabling filtering where coarse sand traps particulate matter for consumption without excess fouling (Bland et al, 2019), and burying to avoid predation (Manderson et al, 1999;Pappal et al, 2012) and damaging storm surge (O'Neill, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the reduction in river sediment flux, up to 160 m of shoreline retreat occurred along the Elwha River delta between 1939 and 2006 21,26 . Shoreline retreat resulted in the development of the cobble low tide terrace as noted above, and this naturally armored feature was formed from relic clasts exposed during the erosion of the coastal plain and also large clasts transported to the lower shoreface from kelp-mediated transport 26,35,39 .…”
Section: The Elwha Littoral Systemmentioning
confidence: 96%